AEROSPACE SYSTEM TRAJECTORY REAL-TIME OPTIMIZATION - Lysenko, Alexander; Tachinina, Olena (Proceedings of National Aviation University (archive), 2019)
Purpose: The purpose of this article is to present the algorithm for calculating the path of two-stage hypersonic unmanned aerial vehicle consisting of unmanned carrier aircraft and unmanned orbital aircraft. Methods: The article describes a method of theory of discontinuous dynamical systems optimal control used to optimize the branching trajectory of a two-stage hypersonic unmanned aerial vehicle. Results: The optimal values of phase coordinates and controls at points of structural transformations of the branching path of a two-stage hypersonic unmanned aerial vehicle are calculated. Discussion: The proposed algorithm allows to optimize the path of two-stage hypersonic unmanned aerial vehicle in any section of the path, including the phase of separation and initial disengagement of orbital stage from air launch aircraft, taking into account the mutual influence of stages.